Acoustic ecology as therapy? - Louise Rossiter (Scottish Journal of Residential Child Care)
As a musician, I have been interested in the potential effects and benefits of music as a therapeutic tool. I have also been in a fortunate position to experience the deployment of music as a 'hands on' tool to interact with children and young people within both communities and residential care settings.